Performance of The Existing Building Under Earthquake Loads Based on Current Indonesian National Standard - Lintang Enggartiasto; Nur Fithriani Fatma Cholida; Purwanto P (JACEE (Journal of Advanced Civil and Environmental Engineering), 2022)
This paper presents the results of an assessment of the existing 5-storey building built in 1980, which aims to determine the level of safety against the most recent standards. The method used is non-destructive testing, collecting planning data in the form of as built drawings and implementation data. The assessment of the existing structure consists of an evaluation of the condition of the material, structural system, and analysis of the structure using the latest load standards. The test results of the existing structural material show that the compressive strength of the concrete still meets the requirements based on SNI-2847-2019. The results of the evaluation of the structure against earthquake loads show that the performance of the structure has a mass participation of 100% and the dynamic base shear force (V) reaches 100% of Vstatic therefore it meets the requirements in SNI 1726-2019. The results of the evaluation of the performance of the structure show that the lateral drift and P-delta effects still meet the requirements of the most recent standards. Horizontal and vertical structural irregularities are found in the existing structural system. The structure's overall performance level (X and Y direction earthquakes) is Damage Control. These results are still permitted for structures with a priority factor (Ie) 1.50, with an earthquake return period of 2500 years.